2009
DOI: 10.1007/s12664-009-0018-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and genotype distribution in patients with hepatitis C virus chronic liver disease

Abstract: This study confirms the preponderance of genotype 3 in Indian patients with HCV related chronic liver disease. Severe steatosis was seen only in genotype 3 and Mallory hyaline was very common in genotype 1. The small numbers of patients in non genotype 3 could be a reason for the apparent lack of histological differences between different HCV genotypes. Severe fibrosis seen in older age groups confirms that HCV infection is progressive and major acceleration of the disease process occurs after 40 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
4
14
0
Order By: Relevance
“…12 In similar studies from India conducted by R. Abraham and A. Chakravarti also showed the most common identifiable risk factor for HCV acquisition was history of surgery followed by blood transfusion. 13,14 The mode of transmission was not identifiable in 10.5% of patients in this study population. A study from India showed that risk factors were not indentified in 22.53% of patients.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…12 In similar studies from India conducted by R. Abraham and A. Chakravarti also showed the most common identifiable risk factor for HCV acquisition was history of surgery followed by blood transfusion. 13,14 The mode of transmission was not identifiable in 10.5% of patients in this study population. A study from India showed that risk factors were not indentified in 22.53% of patients.…”
Section: Discussionmentioning
confidence: 68%
“…17 In this study, there was no significant association between HCV genotype and the mean level of serum ALT level and serum AST level was found. In a study from India conducted by R. Abraham found that serum ALT level correlated poorly with HCV genotype 13,14 . There was little information regarding the correlation between the HCV genotype and viral load found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In published studies genotype 3 is the commonest genotype in India, accounting for 54%-80% of cases. [135][136][137][138][139][140][141][142][143] Within genotype 3, subtype 3a has been the most frequent in most studies, but a recent report found subtype 3b to be the most prevalent. 144 Studies from northern, eastern and western India have uniformly shown predominance of genotype 3; however, in southern India, both genotype 1 and 3 HCV are prevalent.…”
Section: Genotypes Distribution Of Hcv In Indiamentioning
confidence: 99%
“…152 The major acceleration of the disease process occurs after 40 years of age and severe fibrosis/cirrhosis has been seen in 74.24% of patients above 40 years of age as compared to 33.3% of patients below 40 years (P = 0.001). 137 Data on natural history on HCV infection, and its progression to cirrhosis, in India are very scanty. A study from India showed that the median time to develop cirrhosis was 20 years, and progression to cirrhosis was faster (16 vs. 20 years) in those who acquired infection after the age of 35.…”
Section: Natural History Of Hcv In Indiamentioning
confidence: 99%